Penanganan Pelanggaran Pidana Pemilu oleh Bawaslu Bone: Studi atas Praktik Hukum Pemilu - saharuddin sahar (CV Rewang Rencang, 2025)
This study examines the enforcement of election crime law in Bone Regency, focusing on the role and effectiveness of Bawaslu and Sentra Gakkumdu. The research aims to identify the dominant forms of election violations and analyze the mechanisms used to address them. Using a qualitative-descriptive method, the study gathers data through interviews, documentation, and legal analysis. The findings reveal that the most common violations involve state civil apparatus involvement, vote buying, and the misuse of government facilities. While enforcement efforts adhere to existing legal frameworks, challenges persist, including limited coordination between institutions and time constraints in legal processing. The study concludes that improving legal enforcement in regional elections requires not only regulatory consistency but also stronger institutional synergy and community-based preventive strategies. These insights contribute to the development of a more effective and integrity-driven election law enforcement model.